2005
DOI: 10.1139/t05-036
|View full text |Cite
|
Sign up to set email alerts
|

Thin-layer effects on the CPT qc measurement

Abstract: A numerical analysis is presented to model the cone penetration test (CPT) tip resistance in layered soil. Analyses are performed for two-layer soils composed of either sands with different relative densities or different materials (sand and clay). Parametric numerical modeling is used to determine the distance that a cone senses a new upcoming soil layer interface or a layer interface behind. Analyses are also carried out for a thin sand layer embedded in soft clay. It is seen that the full tip resistance may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…Using numerical analyses, Ahmadi and Robertson (2005) demonstrated that depending on the strength of the soil and the in situ stress, the cone in a CPT can sense a layer boundary at a distance of up to 15 cone diameters ahead and behind. The distance is longer for stiff soils and under low effective stress and is shorter for soft soils and under high effective stress.…”
Section: The Issue Of Transition Zonesmentioning
confidence: 99%
“…Using numerical analyses, Ahmadi and Robertson (2005) demonstrated that depending on the strength of the soil and the in situ stress, the cone in a CPT can sense a layer boundary at a distance of up to 15 cone diameters ahead and behind. The distance is longer for stiff soils and under low effective stress and is shorter for soft soils and under high effective stress.…”
Section: The Issue Of Transition Zonesmentioning
confidence: 99%
“…Hence, the bulk and shear modulus are considered to be stress dependent. and Ahmadi and Robertson (2005) have also used stress dependent Mohr-Coulomb model parameters to numerically predict the cone tip resistance in sand. They suggested the following relations for bulk and shear modulus:…”
Section: Constitutive Law For Sandmentioning
confidence: 99%
“…There have also been some numerical simulations conducted for the analysis of layered effects and the definition of the influence zones around soil interfaces (e.g. van den Berg et al, 1996;Ahmadi & Robertson, 2005;Xu & Lehane, 2008;Walker & Yu, 2010). The first analytical solution for penetration in layered soils was proposed by Vreugdenhil et al (1994), which is an approximate solution for simple linear-elastic media.…”
Section: Introductionmentioning
confidence: 99%